2011
DOI: 10.1111/j.1948-7134.2011.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric and morphological variation between two different populations of Phlebotomus major s.l. from endemic and non-endemic foci of visceral leishmaniasis in Iran

Abstract: Populations of Phlebotomus major were examined in two endemic and nonendemic foci of visceral leishmaniasis in Iran. Based on the shape of the aedeagus and ventrally located hairs of coxite and pharyngeal armatures, two morphotypes were found sympatrically in the endemic area of Borazjan. Significant differences in morphometric survey were observed in at least 11 measured characters. The aedeagus of the non-endemic Miyandoab morphotype, and also of a few specimens from Borazjan, is completely parallel througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…The Phlebotomus ( Larroussius ) major complex comprises six morphologically similar and largely allopatric species ( P. neglectus , P. notus , P. major , P. syriacus , P. wenyoni and P. wui ). Phlebotomus neglectus and P. syriacus are only sympatric in the Middle East, including Turkey [12, 50]. Previously, our studies confirmed this sympatry and suggested the existence of a possible third taxon, using genetic data from the mitochondrial cytochrome oxidase b (Cyt-b) gene and the nuclear marker elongation factor (EF-1α) [12].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The Phlebotomus ( Larroussius ) major complex comprises six morphologically similar and largely allopatric species ( P. neglectus , P. notus , P. major , P. syriacus , P. wenyoni and P. wui ). Phlebotomus neglectus and P. syriacus are only sympatric in the Middle East, including Turkey [12, 50]. Previously, our studies confirmed this sympatry and suggested the existence of a possible third taxon, using genetic data from the mitochondrial cytochrome oxidase b (Cyt-b) gene and the nuclear marker elongation factor (EF-1α) [12].…”
Section: Discussionsupporting
confidence: 69%
“…is well documented [5254], the robust discrimination between its component members is crucial for vector incrimination studies. The morphological characters were shown to be insufficient for a specific delimitation [12, 50] but high interspecific genetic distances between the five lineages distributed in Turkey (4.1–13.0%) suggests that cox 1 barcoding is a useful method to discriminate between the members of the ‘Major Group’. Further comparative analysis of the additional nuclear markers and ecological data is necessary to clarify the taxonomic status of its sympatric members.…”
Section: Discussionmentioning
confidence: 99%
“…Within the subgenus Larroussius, P. major (s.l. ), also referred to as "major group", represents a species complex that comprises six genetically distinct species with similar morphology [89,90]. Within this complex, P. major is expected to occur in India, Nepal and Pakistan; we may therefore assume that the historically recorded P. major specimens were in fact P. neglectus that is the only species of the complex occurring in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Even if most sand fly species can be distinguished morphologically it requires expertise to discern these differences. For instance, it is difficult to distinguish P. perniciosus from Phlebotomus longicuspis (Pesson et al , 2004) or Phlebotomus neglectus from Phlebotomus syriacus (Badakhshan et al , 2011; Erisoz Kasap et al , 2013). For damaged specimens and immature stages, molecular methods will be required for accurate identification.…”
Section: Introductionmentioning
confidence: 99%